Extração hidroetanólica de antioxidantes de folhas de moringa oleifera LAM e sua aplicação em substituição à conservante químico em embutido cárneo tipo mortadela - Francelin, Maria Fernanda (2015)
: Hydro-ethanol extracts of the leaves of Moringa oleifera were evaluated for antioxidant capacity so that their most efficient use as a natural preservative could be detected. The extracts of Moringa oleifera leaves were evaluated by quantification methods of total phenolic compounds and evaluation of EC50 by the scavenging capacity of DPPH radical. Analyses and results were outlined and optimized by the statistical program Design Expert 7.1. The extract with the highest antioxidant activity rate (EC50 = 12.43%) was applied to chicken mortadella formulations with 0.25%, 0.50% and 1.00% extract concentrations; control consisted of a sample with 0.25% sodium erythorbate. The different mortadella formulations were evaluated by centesimal, microbiological, sensory and lipid oxidation analyses for 120 days. There was a lower lipid oxidation rate in the formulation with 0.25% extract. Results showed that the extract could inhibit lipid oxidation.